Improving Islamic Education Learning Through the Method of Giving Learning Assignments and Recitation at SD Negeri 1004 Gunung Intan - Surlan; Hasibuan, Evi Fitriwati; Siregar, Mawarni (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve student learning outcomes in Islamic religious education learning by using the method of giving learning assignments and recitations. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subject of this research is elementary school students. The data of this study was obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with research success indicators. The results of the study show that the method of giving learning assignments and recitation can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completeness in each cycle with details of the pre-cycle of 40.19%, the first cycle of 64.37% and in the second cycle it increased to 88.62%. Thus, the use of the method of giving learning assignments and recitation can be used as an alternative to improve student learning outcomes in Islamic religious education learning.